1997
DOI: 10.1007/bf03347996
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive, video-assisted parathyroid surgery for primary hyperparathyroidism

Abstract: A new video-assisted surgical procedure for treatment of primary hyperparathyroidism combined with intraoperative quick PTH measurement was developed. This procedure was successfully used in 6 patients with a single parathyroid adenoma preoperatively localized by neck ultrasound examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
1
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 3 publications
2
118
1
9
Order By: Relevance
“…A considerable recent surge has occurred in the development of endoscopic techniques in thyroid surgery. Since Gagner (7) and Hüscher et al (1) first reported successful endoscopic neck surgery in 1996 and 1997, several endoscopic thyroid surgical techniques have been developed (8)(9)(10)(11)(12)(13)(14). Minimizing surgical stress, cosmetic concerns and improving the postoperative quality of life are the main motivations for developing novel endoscopic thyroid surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable recent surge has occurred in the development of endoscopic techniques in thyroid surgery. Since Gagner (7) and Hüscher et al (1) first reported successful endoscopic neck surgery in 1996 and 1997, several endoscopic thyroid surgical techniques have been developed (8)(9)(10)(11)(12)(13)(14). Minimizing surgical stress, cosmetic concerns and improving the postoperative quality of life are the main motivations for developing novel endoscopic thyroid surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the wide use of sensitive preoperative localization studies some surgeons have advocated the use of a unilateral Figure 1 Plasma PTH (percent of the highest pre-excision value) in the 22 patients with a .50% decrease at T-10, but not at T-5. approach (11 -13), or even minimally invasive (14), video-assisted parathyroid surgery (10,15), the potential benefits of these procedures being the decreased risk of postoperative hypocalcemia, nerve injury and shorter operating time (16 -18). The main limitation of these latter procedures is the possibility of a multiglandular disease in up to 15 -20% of cases of sporadic PHPT, a condition that cannot often be identified preoperatively (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and thirty patients, selected on the basis of preoperative imaging (neck ultrasound and/or 99m Tc-sestamibi) indicating the presence of a single adenoma, absence of goiter, and no previous neck surgery, underwent minimally invasive video-assisted parathyroidectomy (10), and 76 underwent a standard cervical approach. A suspected enlarged parathyroid gland was removed and submitted to frozen section only if the QPTH intraoperative measurement did not show a significant decrease (see below); normal-looking glands were not routinely biopsied.…”
Section: Patientsmentioning
confidence: 99%
“…Many reports on the use of this technique in thyroid surgery, particularly for eliminating the unattractive scars sometimes caused by conventional surgery, have been published. [1][2][3][4][5][6][7][8][9][10][11] Minimal-access thyroid surgery was conceived primarily in Europe and Asia. A number of groups [11][12][13][14][15][16][17] have made pioneering contributions to this field.…”
Section: Introductionmentioning
confidence: 99%